2009
DOI: 10.1124/mol.108.054262
|View full text |Cite
|
Sign up to set email alerts
|

Site Specificity of Agonist and Second Messenger-Activated Kinases for Somatostatin Receptor Subtype 2A (Sst2A) Phosphorylation

Abstract: Somatostatin receptor subtype 2A (sst2A) mediates many of the endocrine and neuronal actions of somatostatin and is the target of somatostatin analogs in cancer therapy. As with many G-protein-coupled receptors, agonist stimulation causes sst2A receptor desensitization and internalization, events that require receptor phosphorylation. Furthermore, heterologous receptor activation of protein kinase C (PKC) also increases sst2A receptor phosphorylation and internalization. Here we analyzed a series of sst2A rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 36 publications
2
44
0
Order By: Relevance
“…This can lead to differences in receptor phosphorylation "barcoding" that can go on to target receptors for different signaling pathways. Cell-type dependence is observed for phosphorylation of different residues in somatostatin type 2A receptors when studied in Chinese hamster ovary, pituitary, and GH4C1 cells (Liu et al, 2009). Likewise, different cell type-dependent phosphorylation of muscarinic m3 receptors has been observed (Torrecilla et al, 2007).…”
Section: Tm Receptors As Shapeshifting Proteinsmentioning
confidence: 83%
“…This can lead to differences in receptor phosphorylation "barcoding" that can go on to target receptors for different signaling pathways. Cell-type dependence is observed for phosphorylation of different residues in somatostatin type 2A receptors when studied in Chinese hamster ovary, pituitary, and GH4C1 cells (Liu et al, 2009). Likewise, different cell type-dependent phosphorylation of muscarinic m3 receptors has been observed (Torrecilla et al, 2007).…”
Section: Tm Receptors As Shapeshifting Proteinsmentioning
confidence: 83%
“…Moreover sst 2 was more rapidly dephosphorylated and recycled after pasireotide treatment than ss14 treatment (Kao et al 2011). It has also been shown that GRK2 is required for ss14-stimulated sst 2 phosphorylation on Ser341/343 (Liu et al 2009) and that GRK2/GRK3 are required for ss14-dependent phosphorylation of sst 2 on Thr353/354 (Pöll et al 2010). Furthermore, overexpression of GRK2 increases pasireotide-dependent phosphorylation and internalization of sst 2 (Pöll et al 2010).…”
Section: Time Course Of Sst 2 Phosphorylation With Pasireotide and Ocmentioning
confidence: 88%
“…sst2 was phosphorylated and internalized after treatment with SRIF and sst2-specific agonists in stable sst2 transfectant GH4C1 cells (Hipkin et al 1997). sst2 is phosphorylated at five serine and threonine residues within the C-terminus following SRIF treatment (Liu et al 2009). Moreover, in transiently transfected GH 3 cells, both SRIF and octreotide, but not pasireotide, induced robust sst2 phosphorylation.…”
Section: Receptor Phosphorylation Internalization and Desensitisationmentioning
confidence: 99%